Antimicrobial resistance profiles ofShigella dysenteriaeisolated from travellers returning to the UK, 2004–2017. Issue 8 (August 2018) - Terry, Lauren M.; Barker, Clare R.; Day, Martin R.; Greig, David R.; Dallman, Timothy J.; Jenkins, Claire
Abstract : Purpose. : Antimicrobial resistance (AMR) profiles of 754 strains of Shigella dysenteriae isolated between 2004 and 2017 from UK travellers reporting symptoms of gastrointestinal (GI) disease were reviewed to look for evidence of emerging AMR associated with travellers' diarrhoea. Methodology. : A travel history was provided for 72.7 % (548/754) of cases, of which 90.9 % (498/548) reported travel outside the UK within 7 days of onset of symptoms, and 9.1 % (50/498) reported no travel in that time frame. During the course of this study, whole genome sequencing (WGS) was implemented for GI disease surveillance, and we compared phenotypic AMR profiles with those derived from WGS data ( n =133). Results/Key findings. : The phenotypic and genotypic AMR results correlated well, with 90.1 % (121/133) isolates having concordant results to 10 classes of antimicrobials. Resistance to the first‐line drugs commonly used in the treatment of shigellosis was observed throughout the study (ampicillin, 54.1%; chloramphenicol, 33.7 %; sulphonamides, 76.0 %; trimethoprim, 80.0%). Between 2004 and 2017, resistance to all classes of antimicrobials (except the phenicols) increased. The proportion of isolates exhibiting reduced susceptibility to ciprofloxacin increased from 3.8 % in 2004 to 75.7 % in 2017, and this was significantly associated with cases reporting travel to Asia compared to Africa ( P <0.001). Of the 201 sequenced isolates, 3.0 % (20/201) had either bla CTX‐M‐15 or bla CMY‐4 . Conclusions. : Increasing MDR, along with resistance to the fluroquinolones and the third generation cephalosporins, in Shigella dysenteriae causing travellers' diarrhoea provides further evidence for the need to regulatethe use of antimicrobial agents and continuous monitoring of emerging AMR.